화력발전소 347H 스테인리스강 튜브의 신뢰성시험 결과분석 - 이웅근; 김동욱; 박상철 (한국설비안전학회지, 2020)
This paper reveals root cause of repetitive reheat cracking at HAZ in SA213-TP347H stainless steel that is used as reheater and superheater in 500MW coal fired boiler. SA213-TP347H stainless tube was introduced in 2007 and there were few damages and short period of usage. But various unexpected failure has frequently happened mainly in the specific manufacturer's after 1.5 year usage. Micro-component analysis, micro-structure analysis and tensile strength test have been followed for evaluating compliance with recent boiler temperature, pressure and flue gas conditions. Various welding bevel angles and welding variables such as welding velocity, welding current, welding interlayer temperature are adapted for making test specimen. These are tested for corelation between thermal effect and tube crack. After this micro-structure analysis are conducted. Solid Solution Heat Treatment, solution treatment, stabilizing treatment, and stabilizing treatment after solid solution heat treatment are carried out for studying the effect of post-weld heat treatment in 347H stainless steel. After doing these micro-structure and mechanical properties changes have been analyzed. This paper propose optimal welding method, heat treatment and material selection guidelines throughout above activities.
Keywords: Type 347H stainless steel; Reheater Cracking; Diffusion; Heat Treatment; Precipitation Reaction